'I can put my culture on my t-shirt': The value of design and enterprise in Ntaria. (4th July 2022) - St John, Nicola
Abstract: In the Aboriginal community of Ntaria, visual communication is utilized to enhance storytelling, kinship relationships, and cultural knowledge. This research investigates how digital design tools could generate new forms of representation and connection while leading to the creation of employment pathways for young adults. Detailed in this paper is how Ntaria Design, a student-led enterprise was cultivated through a design and enterprise education program run at Ntaria School, part of a three-year participatory action study. From a Western Arrarnta perspective, the value of design, and the resulting development of a design-based enterprise was mediated by Country, culture, and community. This in turn necessitated new ways of teaching, learning, and engaging in research together on-Country. The establishment of Ntaria Design illuminates how design education can build entrepreneurial capacity while enabling Aboriginal youth to engage in commercial pathways on their own terms, and according to their own life-worlds.